'People haven't got that close connection': meanings of loneliness and social isolation to culturally diverse older people. (2nd October 2020) - Morgan, Tessa; Wiles, Janine; Moeke-Maxwell, Tess; Black, Stella; Park, Hong-Jae; Dewes, Ofa; Williams, Lisa Ann; Gott, Merryn
Abstract: Objectives: Social isolation and loneliness among older people are known to have negative effects on health and wellbeing. Few studies, however, have enabled older people to define these concepts in their own terms. This paper based on research in Aotearoa, New Zealand is the first to comparatively outline the meanings of loneliness and social isolation from the perspective of four ethnically diverse groups of older adults (Māori, Pacific, Asian, and NZ European). Method: We interviewed 44 older people and conducted three focus groups with 32 older people. We used thematic and narrative analyses. Results: Loneliness and social isolation were conceptualized as interconnected concepts described as a 'look and feel', a 'state of mind' and as a 'lack of desired companionship'. Participants conveyed sophisticated understandings of the structural underpinnings of both loneliness and social isolation as multi-dimensional, complex, and situated. Conclusions: Older people describe complex and culturally- nuanced understanding and experience of social isolation and loneliness. More culturally appropriate services, greater mental-health support and more service provision on weekends and evenings are needed.